United in defeat: the causes and consequences of identity fusion in football fans - Newson, M (2017)
What motivates extreme pro-group action, such as heroism and self-sacrifice on the battlefield? Despite much scholarly attention in recent years, the question is yet to be fully explained. Recent research suggests that shared dysphoric experiences are one way of generating identity fusion, a visceral sense of 'oneness' between individual and group that has been shown to motivate willingness to fight and die for the group. Using two special populations - British and Brazilian football fans - this thesis investigates the causes and consequences of fusion. Football fan cultures are diverse, globally popular, and ripe for examining intergroup conflict. This thesis focuses on two related components of the 'shared dysphoria pathway' to fusion: emotional arousal (e.g. watching one's team suffer a particularly bitter defeat) and the sense of 'self-transformativeness' that ensues from intense, shared experiences. Across four studies, it is shown that for some individuals, sharing the agony of defeat can be emotionally and physiologically arousing to such a degree so as to transform their sense of personal identity. In turn, this leads to a more porous boundary between group and individual identities, i.e. individuals become 'fused' with their groups. Fused people are documented as engaging in some of the most extreme and potentially dangerous social behaviours we know. Two related consequences of fusion are examined: extreme pro-group action and outgroup hostility. Football hooliganism is a persistent, global problem, which is addressed in a fifth study. This thesis refutes past work suggesting that hooligans are social misfits, instead contending that hooligans are especially fused to their group and motivated to defend their 'brothers-in-arms', which results in outgroup violence. These findings suggest that a more thorough understanding of the causes and consequences of fusion could conceivably impact a great many areas, perhaps most importantly conflict resolution and policies relating to intergroup conflict.